Rationing the Constitution how judicial capacity shapes Supreme Court decision-making - Coan, Andrew (Harvard University Press, 2019)
The Supreme Court is a tiny institution that can resolve only a fraction of the constitutional issues generated by the American government. This simple yet startling fact is impossible to deny, but few students of the Court have seriously considered its implications. In Rationing the Constitution, Andrew Coan explains how the Court's limited capacity shapes U.S. constitutional law and argues that the limits of judicial capacity powerfully constrain Supreme Court decision-making on many of the most important constitutional questions, spanning federalism, separation of powers, and individual rights. Examples include the commerce power, presidential powers, Equal Protection, and regulatory takings. The implications for U.S. constitutional law are profound. Lawyers, academics, and social activists pursuing social reform through the courts must consider whether their goals can be accomplished within the constraints of judicial capacity.--